Struktur Semantik Kata Emosi dalam Bahasa Indonesia - J.E. Prawitasari Hadiyono (Faculty of Psychology, Universitas Gadjah Mada, 2010)
This study examined semantic structure of emotion terms in Indonesia. 45 kind of emotion terms as measured by adjective 10 paires in semantic differential. All emotion term is choosed based on familiarity derived from Indonesian Dictionary. We hypothesized that semantic stucture of emotion terms can be reduced into three dimensions, consistent with semantic differential scale factor by Osgood (evaluation, potency, activity). Based on 115 participant, our findings indicate that structure of emotion terms load in two dimensions by multidimensional analysis (evaluation, activity). For two dimensions loading, multidimen‐sional stress value can be reduced in 0,38. Lower stress value indicate that two dimensions loading for semantic structure of emotion word more appropriate than three dimension. Mapping of a series of emotion terms from a proximities matrix (similarities or dissimilarities) based on semantic structure produced nine cluster of emotion terms in Indonesia.